Serial Electron Diffraction Data Processing With diffractem and CrystFEL - Bücker, Robert; Hogan-Lamarre, Pascal; Miller, R. J. Dwayne (Frontiers in Molecular Biosciences, 2021)
Serial electron diffraction (SerialED) is an emerging technique, which applies the snapshot data-collection mode of serial X-ray crystallography to three-dimensional electron diffraction (3D ED), forgoing the conventional rotation method. Similarly to serial X-ray crystallography, this approach leads to almost complete absence of radiation damage effects even for the most sensitive samples, and allows for a high level of automation. However, SerialED also necessitates new techniques of data processing, which combine existing pipelines for rotation electron diffraction and serial X-ray crystallography with some more particular solutions for challenges arising in SerialED specifically. Here, we introduce our analysis pipeline for SerialED data, and its implementation using the CrystFEL and diffractem program packages. Detailed examples are provided in extensive supplementary code.